Comparison of the Correct Use of Different Types of Inhalers in Patients with COPD and Bronchial Asthma - A. A. Vizel; A. I. Rezyapova; I. Yu. Vizel (Туберкулез и болезни лёгких, 2023)
The objective: to compare the correct use of different types of inhalers in patients with COPD and bronchial asthma.Subjects and Methods. 100 patients with COPD and 108 patients with BA were examined. Nine devices were evaluated – a metered dose inhaler (MDI), Rapihaler, Respimat, Breezhaler, CDM, Turbuhaler, Genuair, Spiromax, and Ellipta. The application technique was assessed before the patient read the use instructions and was governed by his intuition, after reading the use instructions, and after training in the inhalation technique by the investigating physician.Results. When COPD patients used inhalers by intuition, they managed to use them successfully in more than 30% of cases with Ellipta, Breezhaler, and Spiromax. After reading the use instructions, the correct use was achieved in 80% of cases when using CDM inhaler, Spiromax, Genuair, and Ellipta. Training conducted by the physician resulted in 100% success rate for Spiromax, Genuair, Ellipta, Breezhaler, and CDM inhaler. With asthma patients using inhalers by intuition, the correct use was observed in more than 50% of cases with Spiromax, Ellipta, Rapihaler, and MDI. After reading the instructions, the correct use was achieved in 80% of cases with CDM inhaler, Spiromax, Ellipta, CDM inhaler, Breezhaler, and Genuair. Training conducted by the physician allowed achieving 100% success rate for Spiromax, Ellipta, Breezhaler, and CDM inhaler.Conclusion. Inhalers vary significantly by the patients’ ability to use them correctly. Asthma patients master the correct inhalation technique better versus COPD patients. Liquid inhalers were more difficult to be used correctly, and the best results were observed with multi-dose powder inhalers. The patient’s training by a healthcare professional is critical to assure the correct use of inhalers.